Cardiac Remodeling: Endothelial Cells Have More to Say Than Just NO - Segers, Vincent F. M.; Brutsaert, Dirk L.; De Keulenaer, Gilles W. (Frontiers in Physiology, 2018)
The heart is a highly structured organ consisting of different cell types, including myocytes, endothelial cells, fibroblasts, stem cells and inflammatory cells. This pluricellularity provides the opportunity of intercellular communication within the organ, with subsequent optimization of its function. Intercellular cross-talk is indispensable during cardiac development, but also plays a substantial modulatory role in the normal and failing heart of adults. More specifically, factors secreted by cardiac microvascular endothelial cells modulate cardiac performance and either positively or negatively affect cardiac remodeling. The role of endothelium-derived small molecules and peptides – for instance NO or endothelin-1 – has been extensively studied and is relatively well defined. However, endothelial cells also secrete numerous larger proteins. Information on the role of these proteins in the heart is scattered throughout the literature. In this review, we will link specific proteins that modulate cardiac contractility or cardiac remodeling to their expression by cardiac microvascular endothelial cells. The following proteins will be discussed: IL-6, periostin, tenascin-C, thrombospondin, follistatin-like 1, frizzled-related protein 3, IGF-1, CTGF, dickkopf-3, BMP-2 and -4, apelin, IL-1β, placental growth factor, LIF, WISP-1, midkine, and adrenomedullin. In the future, it is likely that some of these proteins can serve as markers of cardiac remodeling and that the concept of endothelial function and dysfunction might have to be redefined as we learn more about other factors secreted by ECs besides NO.